2016
DOI: 10.1080/10426914.2016.1198018
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations in powder mixed electric discharge machining of Ti–35Nb–7Ta–5Zrβ-titanium alloy

Abstract: The present research is the first type of study, in which the application of powder mixed electrical discharge machining (PM-EDM) for the machining of β-phase titanium (β-Ti) alloy has been proposed. β-Ti alloys are new range of titanium alloys, which has wide spread application in dental, orthopaedics, shape memory, and stents. The aim of the present study is to fabricate submicro-and nano scale topography by PMEDM process to enhance the biocompatibility without affecting machining efficiency. The effect of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(62 citation statements)
references
References 45 publications
5
53
0
Order By: Relevance
“…A study on the EDM of -Ti-alloy presented by Prakash et al [160] revealed a higher cell growth and adhesion on the machined surface. In similar studies, carbide and oxide layers which enhance the biocompatibility of -Ti-alloy were achieved when Sipowder was added to the EDM dielectric fluid [11]. It was also proven that the nanoporosities fabricated by PM-EDM process promote the cell growth and adhesion [161,162].…”
Section: Biocompatible and Bioactive Oxide Layer Formationmentioning
confidence: 71%
See 2 more Smart Citations
“…A study on the EDM of -Ti-alloy presented by Prakash et al [160] revealed a higher cell growth and adhesion on the machined surface. In similar studies, carbide and oxide layers which enhance the biocompatibility of -Ti-alloy were achieved when Sipowder was added to the EDM dielectric fluid [11]. It was also proven that the nanoporosities fabricated by PM-EDM process promote the cell growth and adhesion [161,162].…”
Section: Biocompatible and Bioactive Oxide Layer Formationmentioning
confidence: 71%
“…It was also reported that the white layer thickness decreases with a decrease in pulse duration (electrical energy) [152]. In addition, an EDM automatic finishing setting and the addition of powder to the dielectric fluid reduced the formation of a recast layer [11,153,154] as depicted in Figure 18.…”
Section: Formation and Influence Of Recast Layer On Edmedmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, the interpretations of this decreasing are the same. Furthermore, this behavior is also recognized in trials (9,11) and (13,15), respectively. The active role of NCP particles in experiments (6,8) is continuous and reflects on the TWR for the copper electrode.…”
Section: Influence Of Spark Heat On Twr Performancementioning
confidence: 60%
“…This research field is treated with various responses including the wear rate of the electrode and it is considered as one of the most significant responses in PMEDM. Most of the studies proved to decrease the Tool Wear Rate (TWR) upon the addition of the powder particles to the dielectric liquid in EDM [10][11][12]. The mixing of the powder particles with the dielectric fluid does not represent a final solution to the problems of EDM.…”
Section: Introductionmentioning
confidence: 99%